Self-inflicted harm in custody, Australia, 1989 - Biles, David (ADA Dataverse, 2018)
This study is one of several studies conducted for a Royal Commission inquiry into aboriginal deaths in custody. The purpose of the study was to obtain information on self-inflicted harm in custody. The interest was in both attempted suicide (whether the person actually intended to die from the attempt or not) and other forms of self-harm, such as lacerations. It was intended that the information could be used to help develop policies and practices that may reduce the incidence of self-inflicted deaths in custody. Topics covered in the present study include the time, place and form of self-injury, the immediate reaction of custodial staff and subsequent action (e.g. bail to attend hospital, counselling), and the use of alcohol or drugs. Background variables include geographical location and the age, sex, race (aboriginal or nonaboriginal) and most serious offence of the offender. Aboriginal and Torres Strait Islander people, researchers and other users should be aware that material in this dataset may contain material that is considered offensive. The data have been retained because it represents an evidential record of language, beliefs or other cultural situations at a point in time.